2009
DOI: 10.1002/hipo.20653
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amygdala kindling on hippocampal neurogenesis coincides with decreased reelin and DISC1 expression in the adult dentate gyrus

Abstract: Temporal lobe seizures can induce the proliferation and abnormal migration of newly generated dentate granule cells, but little is known about the molecular mechanisms that govern these pathological events. Reelin and DISC1 (disrupted-in-schizophrenia 1) are proteins that play a regulatory role in the maturation and integration of new neurons in the developing and adult brain. In this study, we examined whether amygdala kindling results in aberrant neurogenesis and altered expression of reelin and DISC1 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 74 publications
3
27
0
Order By: Relevance
“…Interestingly, limbic-kindled rats also had significantly more DCX-ir cells containing basal dendrites. These findings are consistent with previous reports that seizures facilitate dendritic outgrowth and the presence of hilar basal dendrites [16,17,54,55]. What mechanisms may account for this hypertrophic dendritic growth?…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Interestingly, limbic-kindled rats also had significantly more DCX-ir cells containing basal dendrites. These findings are consistent with previous reports that seizures facilitate dendritic outgrowth and the presence of hilar basal dendrites [16,17,54,55]. What mechanisms may account for this hypertrophic dendritic growth?…”
Section: Discussionsupporting
confidence: 94%
“…Previous reports have indicated that limbic seizures downregulate the expression of migratory proteins, such as the extracellular matrix protein reelin and the susceptibility gene disrupted in schizophrenia 1 (DISC1), in the SGZ or GCL [16,52,53]. This likely contributes to aberrant migration of adult generated neurons after limbic kindling.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations